PENGARUH POTONGAN HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI PELANGGAN DI PT. PLN UP3 BAUBAU (STUDI PADA PROGRAM “NYAMAN KOMPOR INDUKSI”) - Iqbal Nur, Muhammad; Hasni, Hasni; Zarliani Uli, Nur (JIM : Journal Of International Management, 2024)
This research aims to find out whether price discounts influence purchase interest, service quality influences purchase interest and whether price discounts and service quality simultaneously influence purchase interest at PT. PLN UP3 Baubau. This research uses a quantitative method. The population in this research is all customers of PT. PLN UP3 Baubau which uses the "comfortable Induction Stove" program. The sampling technique used the Slovin method with the calculation results finding a sample of 77 respondents. The results of this research show that price discounts have a significant effect on buying interest, from the results of the t test the significance value of the price discount variable is 0.005 < 0.05. Furthermore, the calculated t value > t table is 2.886 > 1.668. The service quality variable shows a significant influence on purchase interest with the t test results having a significance value of 0.000 < 0.05 and the calculated t value > t table, namely 5.745 > 1.668. The results of the f test show that there is a significant influence of the price discount and service quality variables simultaneously on purchasing interest where the significance value is 0.000 < 0.05 and the calculated F value > F table, namely 62.849 > 3.12. The results of the coefficient of determination test obtained an Adjusted R Square value of 0.619. This figure means that the price discount variable (X1) and the service quality variable (X2) simultaneously (together) have an effect on the purchase interest variable (Y) by 61.9%. Meanwhile, the remaining 38.1% was influenced by other variables that were not studied